Performance study of lead-acid battery in a solar car under different traffic and weather conditions - Mahmud, Abdullah Al; Jafar, Imran Bin; Zaman, Asif; Rahman, Mosaddequr Abdur (© 2016 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 4th International Conference on the Developments in Renewable Energy Technology, ICDRET 2016; Dhaka; Bangladesh; 7 January 2016 through 9 January 2016 [© 2016 UIU] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICDRET.2016.7421475